The true identity of the Gymnosphaera gigantea (Cyatheaceae) in China - Dong, Shi-Yong; Haque, Kamrul; Rahman, Mohammad Sayedur (Phytotaxa, 2020)
The scaly tree fern widely accepted as Gymnosphaera gigantea in China is demonstrated to be a separate species, G. henryi. Our field observations show that G. henryi is a good species and is readily recognized by the combination of stipe bearing 2-rowed scales throughout, pinnae being sessile, and most or at least lower pinnae being opposite on rachis. However, G. gigantea is different in stipe without 2-rowed scales above the base and pinnae being more or less petiolate and mostly alternate on rachis. Gymnosphaera henryi is common in southern and southwestern China and Vietnam and is currently known also in Laos and Myanmar.